2014
DOI: 10.3390/molecules19044595
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant and Cytotoxic Activity of Some Synthetic Riparin-Derived Compounds

Abstract: This study aimed to study the in vitro antioxidant activity and cytotoxicity on tumor cells lines of six synthetic substances derived from riparins. All the substances showed antioxidant activity and riparins C, D, E, F presented cell growth inhibition rates greater than 70%, suggesting that these molecules have antitumor properties. These substances also caused greater than 80% releases of cytoplasmic lactate dehydrogenase enzyme (LDH). Although the antioxidant and antitumor properties presented herein requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
1
20
0
7
Order By: Relevance
“…The water molecules serve to link molecules forming two-dimensional array ( In using natural sources as the basis to develop new drugs, industry usually faces the challenge of low concentrations of selected substances that generally make their commercial exploitation unfeasible. However, the synthesis of these substances and their derivatives frequently allow the pharmacophore to be established, and modulation of biological profiles represent an excellent opportunity to explore the biological actions of these synthetic and semi-synthetic compounds [28]. In using natural sources as the basis to develop new drugs, industry usually faces the challenge of low concentrations of selected substances that generally make their commercial exploitation unfeasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water molecules serve to link molecules forming two-dimensional array ( In using natural sources as the basis to develop new drugs, industry usually faces the challenge of low concentrations of selected substances that generally make their commercial exploitation unfeasible. However, the synthesis of these substances and their derivatives frequently allow the pharmacophore to be established, and modulation of biological profiles represent an excellent opportunity to explore the biological actions of these synthetic and semi-synthetic compounds [28]. In using natural sources as the basis to develop new drugs, industry usually faces the challenge of low concentrations of selected substances that generally make their commercial exploitation unfeasible.…”
Section: Resultsmentioning
confidence: 99%
“…In using natural sources as the basis to develop new drugs, industry usually faces the challenge of low concentrations of selected substances that generally make their commercial exploitation unfeasible. However, the synthesis of these substances and their derivatives frequently allow the pharmacophore to be established, and modulation of biological profiles represent an excellent opportunity to explore the biological actions of these synthetic and semi-synthetic compounds [28].…”
Section: Resultsmentioning
confidence: 99%
“…There are compounds [42] (Nunes et al, 2014), including diterpene and carnosic acid (C 2 0H 28 O 4 ), that have antioxidant activity due to the presence of active -OH groups [43]. There are a number of commercially used natural antioxidants, including some diterpenes-kahweol, cafestol [44], carnosic acid, and carnosol [19], and oxidation products of carnosic acid (rosmanol and isorosmanol) [45].…”
Section: Study-based Conclusive Talksmentioning
confidence: 99%
“…The group of this study previously showed that synthetic riparins (A-F) have antiproliferative potential (Nunes et al 2014). In this study, cytotoxic activity was confirmed in other cancer cell lines, with selective effect on colon carcinoma.…”
Section: Discussionmentioning
confidence: 52%
“…Tests regarding its antioxidant and myorelaxing effects in animal models indicated that riparin A has neuroprotective capacity, without reducing the muscle tone of rodents (Nunes et al 2014;. Riparin A has also recently demonstrated antiinflammatory potential in acute inflammation models, in which it reduced inflammatory response through inhibition of cellular events, neutrophils migration modulation and inhibition of proinflammatory cytokines (TNF-α and IL-1β) production.…”
Section: Introductionmentioning
confidence: 99%